Carmelo Giuseppe Conticello and Vassa Conticello (eds.), La Théologie byzantine et sa tradition. Tomo 2. (XIIIe-XIXe siècles). (Corpus Christianorum.) Turnhout: Brepols, 2002. ISBN 2 503 51061 2 - Panagopoulos, Spyros P. (De Medio Aevo, 2020)
Reseña del libro de Carmelo Giuseppe Conticello and Vassa Conticello (eds.), La Théologie byzantine et sa tradition. Tomo 2. (XIIIe-XIXe siècles). (Corpus Christianorum.) Turnhout: Brepols, 2002. ISBN 2 503 51061 2